PENGARUH LINGKUNGAN PSIKOLOGIS DAN SOSIAL-BUDAYA TERTANGGUNG TERHADAP KINERJA STRATEGI PEMASARAN ASURANSI KERUGIAN (Fokus Ekonomi, 2009)
The insured’s psychological field that involved personality, learning, perception, motivation and attitude, and the insured’s socio-cultural environment that involved culture, demography, reference group, family and social status, influenced to the general insurance companies’s markating strategy performance, and affects to  the insured’s decision making. A survey was  conducted in 2002,  to  around 400  motor  vihicle policy holder’s from over 40 general  insurance companies  (living) in Daerah Khusus Ibukota Jakarta Raya. It concluded that the insured’s psychological field and  socio-cultural environment,  influence the marketing strategy for some 54,76% and 20,25%. Beside the insured’s psychological field, sociocultural environment and general insurance companies’s marketing strategy  affects to the  insured’s decision making for some 17,64%, 28,09% and 37,21%  respectively.